2016
DOI: 10.1016/j.talanta.2015.10.053
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of microwave-assisted fusion and microwave-assisted acid digestion methods for determining elemental impurities in carbon nanostructures using inductively coupled plasma optical emission spectrometry

Abstract: It is common for as-prepared carbon nanotube (CNT) and graphene samples to contain remnants of the transition metals used to catalyze their growth; contamination may also leave other trace elemental impurities in the samples. Although a full quantification of impurities in as-prepared samples of carbon nanostructures is difficult, particularly when trace elements are intercalated or encapsulated within a protective layer of graphitic carbon, reliable information is essential for reasons such as quantifying the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 35 publications
0
25
1
Order By: Relevance
“…These are notoriously difficult to eliminate and may affect the physical properties of the sample. 7,8 Even though ''puried'' CNTs are available commercially, it is sometimes challenging to nd trustworthy information regarding the content of metals and/or the lot-to-lot compositional homogeneity. [9][10][11][12] While this may not constitute a critical issue in applications such as mechanical reinforcement of polymers, in other cases such as electrocatalysis, it can lead to erroneous data interpretation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These are notoriously difficult to eliminate and may affect the physical properties of the sample. 7,8 Even though ''puried'' CNTs are available commercially, it is sometimes challenging to nd trustworthy information regarding the content of metals and/or the lot-to-lot compositional homogeneity. [9][10][11][12] While this may not constitute a critical issue in applications such as mechanical reinforcement of polymers, in other cases such as electrocatalysis, it can lead to erroneous data interpretation.…”
Section: Introductionmentioning
confidence: 99%
“…15,18 Concurrent with these advances, some of us proposed alkaline oxidation (or "fusion") as an alternative approach to disintegrate CNTs for ICP-based analyses. 8 This treatment is normally applied to samples that are impervious to strong acids. Among these are refractory materials such as carbides 19,20 and borides, ceramics, 21 mineral ores, 22,23 marine sediments 24,25 and human bones.…”
Section: Introductionmentioning
confidence: 99%
“…However, because the obtained data on the size distribution are similar to those obtained from aqueous suspension of MWCNTs containing Tween 80 (Takaya et al, 2010), it is suggested that the size distributions are not practically different regardless of the vehicle, if MWCNTs are sufficiently dispersed. For the determination of the metal contents of MWCNTs, the elution of metals from MWCNTs requires the strong acidic condition at a high temperature (Fenoglio et al, 2008;Patole et al, 2016), and metals are not eluted in the aqueous solution under the neutral pH. It is thus suggested that the metal contents of MWCNTs in 2% CMC solution (administering to rats) are dependent on the concentration of MWCNTs.…”
Section: Discussionmentioning
confidence: 99%
“…fusion) is also capable to digest different types of carbons. 7 The ICP-OES readings from the fusion procedure were compared with those of microwave-assisted acid digestion, but the outcome was not entirely conclusive. In a follow-up study, we validated fusion for ICP-OES by resorting to a chemically certified reference material (CRM), the SWCNT-1, and a lithium (meta)borate salt.…”
Section: Introductionmentioning
confidence: 99%